Army public health and preventive medicine: Proactive approaches to readiness - Cates, Michael B (My University, 2009)
Preventive medicine is crucial in maintaining the readiness of our most important resource—our people. Sustaining, and even improving, a Soldier’s health is a much wiser use of resources than waiting until that Soldier becomes sick or injured before attempting to restore health. The better we prevent diseases, conditions and injuries, the more resources will be available to apply to those things we cannot prevent. While there is continuing and growing emphasis on proactive approaches to health in today’s society and military, we must all strive toward translating that into real, even greater long-term nvestments in the future of our personnel. Prevention is the best way to health.
Keywords: Military public health; Preventive medicine; Proactive approaches to readiness; Prevention; Enhance readiness; Health threats